Adipose-Derived Stromal Cell-Sheets Sandwiched, Book-Shaped Acellular Dermal Matrix Capable of Sustained Release of Basic Fibroblast Growth Factor Promote Diabetic Wound Healing - Shi, Xin; Jiang, Liyuan; Zhao, Xin; Chen, Bei; Shi, Wei; Cao, Yanpeng; Chen, Yaowu; Li, Xiying; He, Yusheng; Li, Chengjie; Liu, Xiaoren; Li, Xing; et al. (Frontiers in Cell and Developmental Biology, 2021)
The management of diabetic wounds is a therapeutic challenge in clinical settings. Current tissue engineering strategies for diabetic wound healing are insufficient, owing to the lack of an appropriate scaffold that can load a large number of stem cells and induce the interaction of stem cells to form granulation tissue. Herein we fabricated a book-shaped decellularized dermal matrix (BDDM), which shows a high resemblance to native dermal tissue in terms of its histology, microstructure, and ingredients, is non-cytotoxic and low-immunogenic, and allows adipose-derived stromal cell (ASC) attachment and proliferation. Then, a collagen-binding domain (CBD) capable of binding collagen was fused into basic fibroblast growth factor (bFGF) to synthetize a recombinant growth factor (termed as CBD–bFGF). After that, CBD–bFGF was tethered onto the collagen fibers of BDDM to improve its endothelial inducibility. Finally, a functional scaffold (CBD–bFGF/BDDM) was fabricated. In vitro and in vivo experiments demonstrated that CBD–bFGF/BDDM can release tethered bFGF with a sustained release profile, steadily inducing the interaction of stem cells down to endothelial differentiation. ASCs were cultured to form a cell sheet and then sandwiched by CBD–bFGF/BDDM, thus enlarging the number of stem cells loaded into the scaffold. Using a rat model, the ASC sheets sandwiched with CBD–bFGF/BDDM (ASCs/CBD–bFGF/BDDM) were capable of enhancing the formation of granulation tissue, promoting angiogenesis, and facilitating collagen deposition and remodeling. Therefore, the findings of this study demonstrate that ASCs/CBD–bFGF/BDDM could be applicable for diabetic wound healing.